Stereoselective synthesis of ophiocerins A and C - Show, Krishanu; Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An efficient synthesis of ophiocerins A and C has been achieved via a common intermediate. The stereogenic centers were generated by means of Jacobsen's hydrolytic kinetic resolution and Sharpless kinetic resolution. (C) 2011 Elsevier Ltd. All rights reserved.

Synthesis of ophiocerins A, B and C, botryolide E, decarestrictine O, stagonolide C and 9-epi-stagonolide C employing chiral hexane-1,2,3,5-tetraol derivatives as building blocks - Show, Krishanu; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
An organocatalytic approach to the synthesis of (2R,3S)-hexane-1,2,3,5-tetraol (11) derivatives (in the forms of different stereoisomers and bearing different protecting groups) has been developed. The key chiral intermediates 11 were prepared with complete stereocontrol through the proline-catalyzed intermolecular aldol reaction between acetone and d-glyceraldehyde acetonide. The synthetic utility of the intermediates was demonstrated by their transformation into the title hydroxylated pyrans and a variety of unsaturated lactones through standard synthetic protocols.